Navaratna : eka anuśīlana - Vallabhācārya, 1479-1531? (Vallabha Śodha-Saṃsthāna kā pushpa, 1978)
Nine verses, interpretive notes, on basic tenets of the Śuddhādvaita school in Hindu philosophy and Vallabha sect in Vaishnavism.